Maureen Forrester. Au-delà du personnage. Un récit autobiographique - Forrester, Maureen; McDonald, Marci (Éditions Libre Expression, 1989)
Les petits et grands moments de la vie et de la carrière de l'artiste.
Google-Books-ID: QjWtcQAACAAJ

Les Ursulines et la musique - Gréroire-Reid, Claire; V. -Demers, Micheline (Cap-aux-Diamants : la revue d'histoire du Québec, 1989)
Publisher: Les Éditions Cap-aux-Diamants inc.

Analyse de la composition musicale Coulage - Pelletier, Marie (Université de Montréal, 1989)
Keywords: Pas de lien web

L’Abandon et Mosaïques : deux œuvres musicales, deux parcours - Carignan, Nicole (Université de Montréal, 1988)

Place aux femmes-compositeurs du Québec - Lefebvre, Marie-Thérèse (Les Cahiers de l'ARMuQ, 1988)

Pierrette Alarie et Léopold Simoneau. Deux voix, un art - Maheu, Renée (Éditions Libre Expression, 1988)

Emma Albani (1847-1930) - Potvin, Gilles (Les Cahiers de l'ARMuQ, 1988)

Notes on Violet Archer - Proctor, George A. (Musical Canada: Words and Music Honouring Helmut Kallmann, 1988)
Notes on Violet Archer was published in Musical Canada on page 188.

La création musicale chez les religieuses enseignantes de Montréal - Rhéaume, Claire (Cahiers de l'ARMuQ, 1988)

Éva Gauthier (1885-1958) : première cantatrice canadienne-française d’avant-garde - Turbide, Nadia (Les Cahiers de l'ARMuQ, 1988)

« Sursis», « Play room » [analyses] - Bertrand, Ginette (Université de Montréal, 1987)
Keywords: Pas de lien web

Les femmes compositeurs au Canada : données sociologiques et historiques - Kidd, Roseanne (Sonances, 1987)

L'implication sociale et créatrice de Micheline Coulombe Saint-Marcoux - Lévesque, Carole (Université McGill, 1987)

La création musicale chez les religieuses de trois communautés montréalaises - Rhéaume, Claire (Université de Montréal, 1987)

Out of Character - Forrester, Maureen; McDonald, Marci (McClelland & Stewart Publishing, 1986)

Biographical Study of Eva Gauthier (1885–1958): First French-Canadian Singer of the Avant-Garde - Turbide, Nadia (Université de Montréal, 1986)

Muséalogue : Maryvonne Kendergi - Bail Milot, Louise (1985)
Muséalogue : Maryvonne Kendergi

Au-delà du mur du son, l’univers consonant et dissonant d’Anne Lauber - Cloutier, Diane (La Scène musicale, 1984)

La musique de salon au Québec (1880-1915) - Geoffrion, Diane (Les Cahiers de l'ARMuQ, 1984)

Emma Albani: Victorian Diva - MacDonald, Cheryl (Dundurn Press, 1984)
Talented Emma Albani was a favourite of Queen Victoria, singing at Victoria's funeral as well as Edward VII's coronation, and for many other heads of state from Russia, Austria, France, Italy, Belgium, Denmark, United States and Canada. Sir Arthur Sullivan, Gounod, Von Flotow and Dvorak wrotemusic for her and she sang with Nellie Melba, Adelina Patti, Jean de Reszke, Francesco Tamagno among others. Emma, who married Ernest Gye, manager of Covent Garden, was celebrated as one of the leading operatic and oratorio sopranos of the century. Emma (Lajeunesse) Albani, one of Canada's first internationally known performers, began as a student singing in a Chambly, Quebec convent and an Albany, New York church. From her opera debut in April 1870 in Sicily to her farewell concert in October 1911 in London, England, she was loved for her voice as well as her kindness, which was rare in a prima donna. She was adored by fans world-wide as George Bernard Shaw recorded in 1889," ... people were standing two and three deep behind the chairs ..., consisting of prima donna worshippers who are bent on obtaining a bird's eye view of Madam Albani.

La musique de salon au Québec (1880-1915) - Geoffrion, Diane (Université de Montréal, 1983)

Éva Gauthier. De Java au Jazz - Turbide, Nadia (Aria, 1982)

The Motet in New France: Some 17 th and 18 th Century Manuscripts in Quebec - Schwandt, Erich (Fontes Artis Musicae, 1981)

The Choral Music of Violet Archer - Don Huiner, Harvey (Université d'Iowa, 1980)

Violet B. Archer : une élève canadienne de Bela Bartok - Lenoir, Yves (Institut supérieur d'archeologie et d'histoire de l'art, Université catholique de Louvain, 1980)